A facile strategy for synthesis of spinel ferrite nano-granules and their potential applications. Issue 71 (13th July 2016) - Cao, Derang; Pan, Lining; Li, Hao; Li, Jianan; Wang, Xicheng; Cheng, Xiaohong; Wang, Zhenkun; Wang, Jianbo; Liu, Qingfang
Abstract : A number of spinel ferrite nano-granules were synthesized in DMF through a calcination process under air. Abstract : We have demonstrated a facile method to synthesize a number of spinel ferrite nano-granules in dimethyl formamide (DMF) through a calcination process under air. There is no pH regulation, gas atmosphere, centrifugation, supplementary reagents, or other complicated and cumbersome procedures during the preparing process. The structures, morphologies, and magnetic properties of NiFe2 O4, CoFe2 O4, and NiZnFe2 O4 nano-granules in various DMF concentrations and different calcination temperatures were investigated systematically, and other MFe2 O4 nano-granules were also investigated by this method. As a result, it will cause an impurity phase at low DMF concentration or low calcination temperature, and large quantities of uniform nano-granules will be achieved at about 680 °C in pure DMF. The results show that the method realizes a simple, rapid and convenient route for assembling unitary and binary spinel ferrite nano-granules. In addition, the formation mechanism of the nano-granules was also studied in detail, and DMF plays a dispersing and covering role during the reaction. This synthetic approach also shows great potentiality in the synthesis of maghemite γ-Fe2 O3 with high saturation magnetization, and rare nonmetal-doped CoFe2 O4 is prepared using this strategy. Magnetic properties of doped CoFe2 O4 nano-granules are also improved. These results provide a convenient way for the advancement of magnetic nanomaterials.